MODEL KEPEMIMPINAN VISIONER DAN INTEGRATIF DALAM MENINGKATKAN KOMPETENSI KEPEMIMPINAN - Sugeng Rusmiwari; Agung Suprojo; Dody Setyawan (REFORMASI, 2012)
Legislative behavior have a significant effect on the attitude of apathy Society, Visionary Leadership and harmonious Integrative be one solution which is expected to have a significant impact also on the Public Pelyanan (Prima) Democracy, Visionary Leadership assuming when and Integrative good and harmonious, it means the root of the problem behavior of Arrogance Legislative and public apathy attitude will be solved.